Fick Diffusion Coefficient in Binary Mixtures of [HMIM][NTf2] and Carbon Dioxide by Dynamic Light Scattering and Molecular Dynamics Simulations - Klein, Tobias; Piszko, Maximilian; Kankanamge, Chathura J.; Kasapis, Georgios; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2021)
Dynamic light scattering (DLS) experiments and equilibrium molecular dynamics (EMD) simulations were performed in the saturated liquid phase of the binary mixture of 1-hexyl-3-methylimidazolium bis(trifluormethylsulfonyl)imide ([HMIM][NTf2]) and carbon dioxide (CO2) to access the Fick diffusion coefficient (D11). The investigations were performed within or close to saturation conditions at temperatures between (298.15 and 348.15) K and CO2 mole fractions (xCO2) up to 0.81. The DLS experiments were combined with polarization-difference Raman spectroscopy (PDRS) to simultaneously access the composition of the liquid phase. For the first time in an electrolyte-based system, D11 was directly calculated from EMD simulations by accessing the Maxwell-Stefan (MS) diffusion coefficient and the thermodynamic factor. Agreement within combined uncertainties was found between D11 from DLS and EMD simulations for CO2 mole fractions up to 0.5. In general, an increasing D11 with increasing xCO2 could be observed, with a local maximum present at a CO2 mole fraction of about 0.75. The local maximum could be explained by an increasing MS diffusion coefficient with increasing xCO2 over the entire studied composition range and a decreasing thermodynamic factor at xCO2 above 0.7. Finally, PDRS and EMD simulations were combined to investigate the influence of the fluid structure on the diffusive process.
CRIS-Team Scopus Importer:2021-06-11